Analysis of relevance and effectiveness of FTC-based training: The case of Alamata Woreda, Southern Tigray, Ethiopia - Tekle, L. (Haramaya University, 2010)
FTC-based farmer training is an emerging extension strategy geared towards human capital development through need-based, hands-on practical training in order to facilitate agricultural transformation and rural livelihood improvement. Although FTCs were established and made functional in the Tigray National Regional State and Alamata Woreda no systematic assessment of the relevance and effectiveness of the training were made. Unless the situation of farmers is improved in terms of deciding on their affairs, access to information, exposure to improved farming and practices, all efforts made will be go unrewarding. Hence, to alleviate this problem, educating farmers through basic education intervention and training on improved agricultural and living practices is important. This research was initiated to fill the gap. Specifically the research attempted to address three important questions: What is the relevance and effectiveness of FTC-based training? How do farmers perceive the effectiveness and usefulness of FTC-based training? and Are there FTCs with successful experience for scale-out\up? Primarily quantitative design was employed for the study. The essential data were collected from 65 trained and 65 untrained farmers, 14 DAs and 20 woreda experts by means of semi-structure interview schedule. Qualitative methods that were used at community, organizational and individual levels include: document review, focused/group discussion, personal interviews and direct observation. The quantitative data were also analyzed using descriptive and inferential statistical tools. The results of the study revealed that FTC based training is relevant in terms of timeliness and scheduling specially for male farmers, teaching aids, venue of training, the communication and practical skills of the trainers were also relevant to the farmers. However, FTC based training, lacks training need assessment, less in adequacy and quality of training facilities and being more theoretical and lecture type in methodology, limited use of’ indigenous knowledge, less female participation and follow up after the training were the major deficiencies. The study also showed that trained farmers acquired better knowledge, aspiration, and practice significantly than untrained farmers. Based on the indicators of positive deviance like, departure from the norms, intentional behavior and honorable outcomes such as technology dissemination, exemplary demonstration field management, diversified and substantial training outreaches of the four sampled FTCs, Selambkalsi FTC is found to be positively deviating. In this research context, positively deviant FTC is the one that performed better than the other FTCs regardless of similar problems and resource base. Therefore, it is recommended that policy aimed at FTC based training in the area could be successful if there is proper training need assessment, increases females participations, gives due focus on practice based training, make uses of indigenous knowledge, regular follow up mechanism and the result of this study are taken in to consideration and there should be experience sharing mechanisms among FTCs so as to cross fertilize the successful results throughout the study area and lesson are developed and institutionalized.